An Approach to the Equivalence of Disgust and Grima through the Analysis of Domains and Contexts - Schweiger Gallo, Inge (2024)
Despite the interest in grima during the last years due to its relevance as a culturally specific emotion in Spain, we still lack knowledge about its delineation from the experience of disgust. Applying a combination of deductive and inductive methodologies to the study of grima, it was found that most of the experiences of grima referred to squeaking noises and scratching of surfaces, followed by situations related to the disgust domain of envelope violations. Further, it was also observed that the experiences of grima occurred in a variety of contexts, with the exception of the institutional context, although mainly in the educational context. The theoretical and methodological implications of the present research are discussed.